SISTEM PENDETEKSI DINI HAMA TANAMAN MENGGUNAKAN KAMERA TERMAL BERBASIS TEKNOLOGI INTERNET OF THINGS - musfirahputri lukman (JTRISTE, 2023)
This study aims to create a pest detection system so that plant owners can receive information about plant conditions through an android application. This system detects the temperature of pests found in plants. In this design process, starting from several system designs, namely Use Case Diagrams, Deployment Diagrams, and Block Diagrams. Then implementation of expert systems, implementation of electronic design, and software implementation. After testing and evaluating system performance, the results obtained are 4% error, in other words the accuracy of the pest detection system is 92% and the design of the pest detection system can be implemented based on expert systems.